2012
DOI: 10.1167/iovs.12-9726
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Nerve Fiber Layer Imaging with Spectral-Domain Optical Coherence Tomography: Interpreting the RNFL Maps in Healthy Myopic Eyes

Abstract: The superotemporal and inferotemporal RNFL bundles converged temporally with increasing myopia, which was associated with an increase in area of abnormal RNFL measurement. The interpretation of the RNFL thickness map in myopic eyes requires careful consideration of the distribution pattern of the RNFL bundles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(92 citation statements)
references
References 16 publications
6
84
1
1
Order By: Relevance
“…OCT has emerged as an important imaging tool in the assessment of retinal and optic nerve structure and diseases, such as macular edema, diabetic retinopathy and glaucoma (6,9). The Spectralis OCT accompanied with the eye tracking system allows high-speed, high-resolution imaging of the retina, improves the ability to detect the true inner and outer retinal boundaries and increases repeatability of measurements (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OCT has emerged as an important imaging tool in the assessment of retinal and optic nerve structure and diseases, such as macular edema, diabetic retinopathy and glaucoma (6,9). The Spectralis OCT accompanied with the eye tracking system allows high-speed, high-resolution imaging of the retina, improves the ability to detect the true inner and outer retinal boundaries and increases repeatability of measurements (9).…”
Section: Discussionmentioning
confidence: 99%
“…Parameters measured by optical coherence tomography (OCT) in the myopic eye have been previously studied (4)(5)(6)(7)(8). However, OCT characteristics have not yet been systematically analyzed and compared among different degrees of myopia.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study made on nonglaucomatous eyes with subfoveal drusen and choroidal neovascular membranes we have shown that software version 6.12 in fact significantly improves image segmentation for the GCC scan, compared with the currently available software version (6.3). 23 Image segmentation in high myopia is frequently influenced by myopia-related degenerative changes of the peripapillary retina and the GCC scan area, [14][15][16][17][18] which may reduce the signal-to-noise ratio. We supposed that by imaging nonglaucomatous, OHT, and glaucomatous eyes with high myopia, and analyzing the results with both software versions, respectively, we could investigate if the proposed and previously confirmed 23 benefits of software version 6.12 over the current version represent an advantage for clinical practice and cross-sectional structural classification for glaucoma in highly myopic eyes.…”
Section: Discussionmentioning
confidence: 99%
“…5,8,14 Imaging and classification for glaucoma in high myopia, however, remains a challenge even with Fourier-domain OCT instruments, as retinal thinning due to myopia, peripapillary and posterior pole retina degenerations and staphylomas, vitreomacular adhesions, and other alterations commonly seen in pathologic myopia cause misclassification, artifacts and segmentation errors, and a decrease of RNFLT in nonglaucomatous eyes. [14][15][16][17][18] The RTVue-100 optical coherence tomograph (RTVue-OCT) is one of the Fourier-domain OCT instruments. 3,11,19 Although it has been shown that the reproducibility of the measurements and the diagnostic accuracy for perimetric glaucoma are favorable 3,19,20 ; early detection of glaucomatous progression is possible 11 ; and structurefunction relationship is strong 21 with this instrument, most of the clinical experience with the RTVue-OCT is based on eyes that are not highly myopic.…”
mentioning
confidence: 99%
“…Ohne das Wissen der stär-keren Konvergenz infero-und superotemporaler Bündel könnten Vergleiche mit Referenzkarten normaler Augen zur falsch positiven Anzeige evtl. Bündelde-fekte führen [86]. Im OCT lassen sich außerdem Defekte und Diskontinuitä-ten der Lamina cribrosa darstellen, die ein manifestes Glaukom wahrscheinlicher machen [45].…”
Section: Makulaforamen Und Foveoschisisunclassified